PENGARUH EKOLOGI BERWAWASAN GENDER (KRITIK ECOFEMINISM) DALAM NOVEL MAHLIGAI DIUFUK TIMUR KARYA SUPARTO BRATA - Sutardi Sutardi; Ernaningsih Ernaningsih (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
The aim of this research is to discover (1) the influence of political ecological values (2) the influence of cultural ecological values (3) the influence of social ecological values, and (4) the influence of ecological values inherited from imperialism. The data in this research is data about (1) the influence of political ecological values (2) the influence of cultural ecological values (3) the influence of social ecological values, and (4) the influence of ecological values inherited from imperialism. Data sources were obtained from documentation. The data collection technique is carried out using documentation. Data analysis techniques use interactive techniques. Data validation uses triangulation, both triangulation of theory, data and methods. The results of the research findings can be described as including: (1) the influence of political ecological values (2) the influence of cultural ecological values (3) the influence of social ecological values, and (4) the influence of the ecological values of the legacy of imperialism in the Mahligai novel text in the Eastern Horizon by Suparto Brata.